THE BEHAVIOR OF RARE-EARTH AND LITHOPHILE TRACE ELEMENTS IN RARE-METAL GRANITES: A STUDY OF FLOURITE, MELT INCLUSIONS AND HOST ROCKS FROM THE KHANGILAY COMPLEX, TRANSBAIKALIA, RUSSIA - Badanina E.V.; Trumbull R.B.; Dulski P.; Wiedenbeck M.; Veksler I.V.; Syritso L.F. (My University, 2006)
We have determined trace-element concentrations in fluorite mineral separates, host granites and residual melts trapped in quartz from a well-documented sequence of differentiated Li-F-rich granites in the Khangilay complex, Transbaikalia, Russia, which are associated with Ta (Orlovka) and W (Spokojnoje) mineralization. Fluorite is a common accessory mineral in most units of the granite sequence and in greisen veins from their hydrothermal aureoles. This allows us to monitor the behavior of REE and other fluorite-compatible trace elements during the magma evolution, and to compare magmatic and hydrothermal REE signatures directly. With increasing differentiation of the granites, REE abundances decrease, chondrite-normalized patterns become flat, and negative Eu anomalies more pronounced. Fluorite separates from the respective granites show similar REE patterns and 5-10 times higher concentrations (up to 4000 ppm total REE). First-order features of the whole-rock, fluorite and melt-inclusion REE characteristics are the presence of extreme negative Eu anomalies and the strong lanthanide tetrad effects in the more evolved units. Samples with the tetrad effect also show strong separation of geochemical twin elements (Y-Ho, Zr-Hf). Although melt-inclusion data prove that the lanthanide tetrad effect developed during the magmatic stage, the process cannot be explained by simple fractional crystallization. Partitioning of REE to a F-bearing hydrothermal solution also is unlikely because hydrothermal fluorite from associated veins and greisen does not show complementary W-tetrads. We suggest that the tetrad effect and deviations of element ratios observed in this and other highly evolved F-rich granites are caused by separation of a F-rich hydrosaline melt. This is consistent with results of experimental partitioning studies of immiscible silicate and hydrosaline melts.
Keywords: FLOURITE; HYDROSALINE MELT; IMMISCIBILITY; MELT INCLUSIONS; ORLOVKA; RARE-EARTH ELEMENTS; RARE-METAL GRANITES; RUSSIA; SECONDARY-ION MASS SPECTROMETRY; SPOKOJNOJE; TETRAD EFFECT; TRANSBAIKALIA